Turbulent dispersion of a gas tracer in a nocturnal atmospheric flow. (30th January 2012) - Espinosa, F.; Avila, R.; Raza, S. S.; Basit, A.; Cervantes, J. G.
ABSTRACT: A Lagrangian turbulent dispersion model has been coupled with the Regional Atmospheric Modelling System (RAMS) to predict the transport, dispersion and concentration of a gas tracer released into a stable atmosphere (nocturnal drainage flow) of the Anderson Springs Valley near San Francisco, California. The mean wind velocities governed by the topography of the region and the surface layer fluxes of momentum and heat into the stable atmosphere, were calculated by the RAMS code. The atmospheric transport and dispersion of a gas tracer was simulated in non‐homogeneous turbulence conditions by using a Lagrangian Stochastic Particle Model. A Moving Least Squares technique was used to calculate the tracer gas concentration. The vertical profiles of the mean wind speed and the wind direction, as well as the tracer gas concentration, were compared with the field measurements for the fourth night of the ASCOT experiment (the night between 19 and 20 September 1980) carried out in the Anderson Springs Valley, California, USA The computed profiles for wind direction and wind speed agreed well with the field data. Although at some locations the model predicted strong winds which transported the particle to larger distances downwind, the overall pattern of concentration distribution generated by the model compared quite well with the observations. It was concluded that the concentration patterns tend to follow the topography when the synoptic winds are weak.